Situación laboral de los estudiantes titulados de Psicología Organizacional de la Universidad de las Américas - Andrade Mena, Gabriela Alejandra (2015)
The Psychology School of the UDLA Universidad de las Américas has promoted the investigation about the Current situation of post graduate students in Organizational Psychology, in this context the research was able to identify the positioning of graduated students in the business scope. The main objective of this research was to identify the professional position and follow up post graduate students of the UDLA in the mentioned court. As part of the research the specific objectives were to verify in which areas where the students working and the different functions they perform, also how easy was to obtain a job after graduating and recognize how appropriated was the UDLA syllabus to fit into the current job profile of each post graduate student. It is important to stress that in order to test the hypothesis, the study type was descriptive but it had also a quantitative approach. The sampling was done with 23 UDLA graduated students in Organizational Psychology. The results of the research identified that the sample students are all working in related areas of the career, at the same time it was proved that they did not have problems searching for a job since 100 percent of them worked while they were studying; most of the students does apply the knowledge acquired at the University. This investigation gives important information for the UDLA and the Psychology School so that they can improve the academic field for future students.